The social embeddedness of industrial ecology - Boons, Frank; Howard-Grenville, Jennifer A., 1969-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2009)
Most work on industrial ecology continues to emphasize its roots in engineering and the technological sciences. This book differs in that it explores the social context of industrial ecology and presents empirical work addressing how cognitive, cultural, political and structural mechanisms condition the emergence and operation of industrial ecology. The empirical chapters are written from various social science perspectives and the editors have also invited reflective commentaries by authors with cross-disciplinary experiences.
pt. 1. An outline of the social science potential -- pt. 2. Regional approaches -- pt. 3. Product chain approaches -- pt. 4. The social science contribution reconsidered.
Includes bibliographical references and index.
Keywords: Industrial ecology; Electronic books